Rewriting early Chinese texts - Shaughnessy, Edward L., 1952- (State University of New York Press, 2006)
Rewriting Early Chinese Texts examines the problems of reconstituting and editing ancient manuscripts that will revise-indeed "rewrite"--Chinese history. It is now generally recognized that the extensive archaeological discoveries made in China over the last three decades necessitate such a rewriting and will keep an army of scholars busy for years to come. However, this is by no means the first time China's historical record has needed rewriting. In this book, author Edward L. Shaughnessy explores the issues involved in editing manuscripts, rewriting them, both today and in the past
Keywords: China -- History -- To 221 B.C. -- Sources.; China -- History -- Qin dynasty, 221-207 B.C. -- Sources.; China -- History -- Han dynasty, 202 B.C.-220 A.D. -- Sources.; Paleography, Chinese.; Chine -- Histoire -- Jusqu'à 221 av. J.-C. -- Sources.; Chine -- Histoire -- 221-207 av. J.-C. (Dynastie des Qin) -- Sources.; Chine -- Histoire -- 202 av. J.-C.-220 (Dynastie des Han) -- Sources.; HISTORY.; Paleography, Chinese; China; To 220; History; Sources